Decolonizing nursing through the lens of Black maternal health - Canty, Lucinda (Nursing philosophy, 2023)
In the United States, there is a long history of racial disparities in maternal health, with Black women disproportionately representing poor maternal health outcomes. Black women are three to four times more likely to die from a pregnancy-related complication and twice as likely to experience severe maternal morbidity when compared to white women. Where are nurses in the development of knowledge to improve maternal health outcomes among Black birthing people? This dialogue discusses how decolonizing nursing can occur by examining the history of Black maternal health in the United States and using the works of nursing scholars of color to inform nursing education, research, and clinical practice.